Preparation and Characterization of Bovine Small Intestine Submucosa (SIS) ‎Hydrogel - K Hummadi, Saddam; HR Al-Falahi, Nadia (The Iraqi Journal of Veterinary Medicine, 2023)
The aim of this study was to prepare and characterize a small intestine submucosa (SIS) hydrogel as ‎a bio-scaffold. In this study, SIS from five calves, aged 8-12 months and weighing 250-300 kg, was ‎obtained from a slaughterhouse immediately after slaughtering. The SIS was then decellularized, ‎powdered, and subsequently transformed into a hydrogel. This transformation was achieved by ‎dissolving the decellularized SIS powder in phosphate-buffered saline (PBS) at a concentration of ‎‎50% w/v, and allowing it to form a hydrogel over a 12-hour period at 37 °C. Characterization of the ‎SIS hydrogel was conducted using various techniques. Fourier Transform Infrared Spectroscopy ‎‎(FTIR) was employed to identify the chemical structure of the hydrogel, revealing three primary peaks ‎at 1639 cm-1, 1571 cm-1, and 1338 cm-1, corresponding to amide I, II, and III bands, respectively. ‎Additionally, a broad signal at 3440 cm-1 was observed, indicative of the hydroxyproline side chain. ‎The hydrogel's swelling capacity was evaluated, showing an expansion of 437% after a 12-hour ‎immersion in PBS at a pH of 7.4. Scanning Electron Microscopy (SEM) analysis of the lyophilized ‎hydrogel revealed a highly porous and interconnected architecture, resembling a honeycomb ‎structure. Moreover, the hydrogel's antibacterial efficacy was assessed against Staphylococcus ‎aureus using an agar diffusion test, which demonstrated a zone of inhibition measuring 16.11 mm. ‎The combined chemical, morphological, and antibacterial properties of the SIS hydrogel developed ‎in this study suggest its potential as a promising bio-scaffold for inducing tissue regeneration and ‎restoring tissue function‎.